Enantioselective Construction of Tertiary C(sp3)−P Bonds by Thiourea‐based Bifunctional Phosphonium Salt‐catalyzed Hydrophosphonylation of Ketone Compounds. Issue 17 (9th July 2021) - Feng, Zhenghuai; Zhang, Hongkui; Ren, Xiaoyu; Jiang, Chunhui; Gao, Guowei; Wang, Tianli
Abstract: Asymmetric hydrophosphonylation of carbonyl compounds to generate a variety of optically pure quaternary α ‐hydroxy phosphonate molecules is herein described by thiourea‐derived bifunctional phosphonium salt catalysis. This new synthetic protocol has an excellent functional group tolerance, and particularly both aromatic, heteroaromatic and aliphatic α ‐ketoesters and 1, 2‐diketones were readily transferred into phosphonate products in high yields (up to 99 %) with excellent enantioselectivities (up to 97 % ee). The mechanistic results suggested that both ion pair and hydrogen‐bonding interactions were crucial in asymmetric induction. Abstract : Salt catalysis : A highly enantioselective hydrophosphonylation of carbonyl compounds to generate optically pure quaternary α ‐hydroxy phosphonates and phosphonic acids by thiourea‐derived bifunctional phosphonium salt catalysis has been developed. This new synthetic protocol has an excellent functional group tolerance, and both aromatic, heteroaromatic and aliphatic α ‐ketoesters and 1, 2‐diketones participated well to afford the desired products in high yields (up to 99 %) with good to excellent enantio‐ and/or regioselectivies (up to 97 % ee and >19 : 1 r.r .).